Cocktail: a service-oriented cloud storage architecture for enhancing service quality. (2016) - Chang, Shuchih Ernest; Jang, Yu-Teng Jacky; Shen, Wei-Cheng; Su, Wen-Chi
Cloud computing is getting increasingly popular because of its various benefits. Although many free cloud storage services (such as Google Drive, Dropbox, etc.) are available on the internet, there exist some problems in using such services. Those public cloud storage services can be more convenient and more valuable if those problems are resolved. The first problem is the limitation of the service, such as space limit, file size limit and file type limit. Secondly, different cloud storage services provide different functions so that users may have to use multiple services simultaneously in order to fulfil their needs. The process of logging in and using multiple services might be very complicated. Thirdly, users may not be able to access or even lose their data owing to incidents such as server down, network failure, and availability problems. The goal of this research is to compose a service (named Cocktail) by using the service-oriented computing (SOC) as the fundamental design approach to solve these three problems and enhance the service quality (in terms of the reliability, availability and scalability) of free cloud services.